Calculation of the charged particles trajectories in the hexapole cylindrical field - Saulebekov, A.O.; Assylbekova, S.N.; Kambarova, Zh.T.; Tussupbekova, A.K. (Publishing House of the KarSU named after E.A.Buketov, 2011)
The approximate analytical method of the charged particles trajectories calculations in the hexapole cylindrical field has been described. The trajectories were determining with help of the optimally chosen power series segments superposition, the recurrent relation for the coefficients of the power series was found. It is presented detailed calculation of the charged particles trajectories for a scheme, based on the hexapole cylindrical field, which was not studied earlier. On the proposed methods the corpuscular optical schemes with the hexapole cylindrical field have been calculated. The proposed approximate analytical method allows to describe the trajectories of charged particles in these fields with high accuracy.
Keywords: energy analyzers; hexapole cylindrical field; charged particles; corpuscular optical schemes